Emergence Agitation: Comparison of Paracetamol and Tramadol in Elective Surgery Patients - Thapa, Ajay Singh; Shah, Rakesh; Yadav, Rajesh Kumar; Shrestha, Ram (Journal of National Heart and Lung Society Nepal, 2023)
Background: Post-operative emergence agitation is frequent and self-limiting but at times may present with violent behavior and may result in harm to both patients and caregivers. The objective of this research is to find the incidence of emergence agitation and to compare the effects of paracetamol and tramadol on emergence agitation.Methods: A quasi experimental study was conducted in the Department of Anesthesiology, College of Medical Sciences, Bharatpur, Chitwan, Nepal over a period of three months. One hundred fifty ASA I and II patients aged 18 – 45 years old, posted for elective surgery under general anesthesia were included. Patients were assigned into two equal groups of 75 patients (n=75). At the end of the surgery, group A received inj. tramadol 1mg/kg, just when the surgeon starts skin closure and group B received 15 mg/kg Paracetamol. Time taken for extubation, shivering, Richmond agitation sedation scale (RASS) and sedation and Visual analogue scale (VAS) and need of rescue analgesics were recorded. Results: In paracetamol group, reversal to extubation time was 8.75±3.0 minutes which was higher compared to 6.21±1.84 minutes in tramadol group. Prevalence of shivering was higher in paracetamol group. VAS score in paracetamol group was 5.28±1.03 compared to 4.33±0.82 in tramadol group. Frequency of need of rescue analgesia was higher in paracetamol group. In the immediate postoperative period, agitation was more common. Conclusion: Use of tramadol before extubation reduces the incidence of postoperative emergence agitation, immediate postoperative pain and shivering.